Was Weber Wrong? A Human Capital Theory of Protestant Economic History - Sascha O. Becker; Ludger Wößmann (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Max Weber attributed the higher economic prosperity of Protestant regions to a Protestant work ethic. We provide an alternative theory, where Protestant economies prospered because instruction in reading the Bible generated the human capital crucial to economic prosperity. County-level data from late 19th-century Prussia reveal that Protestantism was indeed associated not only with higher economic prosperity, but also with better education. We find that Protestants' higher literacy can account for the whole gap in economic prosperity. Results hold when we exploit the initial concentric dispersion of the Reformation to use distance to Wittenberg as an instrument for Protestantism.
urn:nbn:de:bvb:19-epub-1366-8
Keywords: N33; Z12; I20; 330; Human capital; Protestantism; economic history; Protestantismus; Bildungsinvestition; Analphabetismus; Entwicklung; Wirtschaftsgeschichte; Wirtschaftssoziologie; Preußen; Deutschland (bis 1945)